2023
DOI: 10.1038/s41598-023-31047-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of interface frictional anisotropy between sand and snakeskin-inspired surfaces

Abstract: The transmission of loads across the soil-structure mobilizes direction-dependent shear resistance, which can be selectively used to design geo-structures. A previous study confirmed the frictional anisotropy induced by the interface between the soil and snakeskin-inspired surfaces. However, it is necessary to estimate the interface friction angle quantitatively. In this study, a conventional direct shear apparatus is modified, and 45 cases are performed in two-way shearing directions between bio-inspired surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The linear and non-linear equations estimated from both studies are shown in (Table 6). As suggested by previous studies, the correlation coefficient higher than 0.8 demonstrate excellent prediction capability of an equation (Lee et al 2023;Nawaz et al 2022 ). Based on this rationale, the results confirm the improved prediction ability of the proposed correlations.…”
Section: Relationships Between Growth Variables and Numbers Of Galls ...supporting
confidence: 85%
“…The linear and non-linear equations estimated from both studies are shown in (Table 6). As suggested by previous studies, the correlation coefficient higher than 0.8 demonstrate excellent prediction capability of an equation (Lee et al 2023;Nawaz et al 2022 ). Based on this rationale, the results confirm the improved prediction ability of the proposed correlations.…”
Section: Relationships Between Growth Variables and Numbers Of Galls ...supporting
confidence: 85%
“…Indeed, the changing trend of interface friction angle is affected by the starting shear direction while the shearing sequence has no effect on the interface friction angle. Previous studies 16,21 revealed that volumetric contraction at the trailing end of the scale during the starting shearing densified soil around the scale, difference in the interface friction angle between the cranial and caudal shearing directions was pronounced depending on the starting shearing direction, and thus the caudal first-caudal second shearing sequence produces larger friction difference than the cranial first-cranial second shearing sequence. However, the current study observes that the interface friction angle in the first shearing cycle is almost identical to that in the second shearing cycle, and thus densification effect during the first shearing is diminished.…”
Section: Evolution Of Interface Friction Anglementioning
confidence: 92%
“…Those potential problems eventually hinder quantifying shear response [28][29][30][31] . Previous study modified the conventional direct shear apparatus for soil-snakeskin-inspired surface tests and soil-soil tests 21 . Fig.…”
Section: Modified Direct Shear Testmentioning
confidence: 99%
See 2 more Smart Citations